The Impact of the New York City Fiscal Crisis on the Interest Cost of New Issue Municipal Bonds - Kidwell, David S.; Trzcinka, Charles A. (Journal of Financial and Quantitative Analysis, 1983)
David S. Kidwell, Charles A. Trzcinka, The Impact of the New York City Fiscal Crisis on the Interest Cost of New Issue Municipal Bonds, The Journal of Financial and Quantitative Analysis, Vol. 18, No. 3 (Sep., 1983), pp. 381-399